Water needs of the banana crop (Musa paradisiaca) Williams variety - Monge-Freile, Marlon Fernando (2022)
In order to establish the evapotranspiration (ETc and the crop coefficient (Kc) for bananas grown under tropical conditions, the water consumption of the crop was measured at 100% of the ETc through drainage lysimeters, and under tropical conditions. of water stress, at 40, 60 and 80% of the ETc. In the critical season (August to December), the water consumption at 100, 80, 60 and 40% of the ETc was 227.78, 79.81, 65.24 and 52.66 mm, respectively, while, in the same conditions evaluated for ETc , the Kc were 1.12, 0.69, 0.53 and 0.36, respectively. The results show that the Kc values recommended by the FAO (Food and Agricultural Organization of United Nations) are lower than the Kc observed in the Ecuadorian coast, so probably the water requirement of bananas is being underestimated.